Realized Access to Antenatal Care Utilization in Uganda: Household Welfare and Governance Implications - Okumu, Ibrahim Mike; Bbaale, Edward (African Journals Online (AJOL), 2016)
The rationale of this study is to explain the link between household welfare, the region in which an infant is situated, literacy level of a mother and malaria prevalence among infants in Uganda with a more recent nationally representative data set that is the 2006 Uganda Demographic and Health Survey in lieu of the findings by other researchers on this particular subject. This was done with the aid of logit model estimation. The findings indicate that the region where an infant situated is fundamental in explaining malaria prevalence among infants. Alongside region is the location of a child whether he or she is in the rural or urban setting, the findings indicate that malaria prevalence lower among urban infants as compared to their rural counterparts. In conclusion, it was observed that malaria prevalence is not a case of household socioeconomic conditions but rather it's a communal disease as exemplified by the significance of region and urban-rural location of an infant.